On the feasibility of landing the dream chaser space vehicle in South Africa - Colvin, Kyle Luke (Department of Electrical Engineering, 2021)
The Dream Chaser is a space vehicle currently under development by the Sierra Nevada Corporation for purposes of carrying humans and cargo to low Earth orbit. In 2016, the United Nations entered into an agreement with Sierra Nevada Corporation to fly experimental payloads on the Dream Chaser. The collaborative UNOOSA-SNC Dream Chaser mission will be approximately two to three weeks in duration, with the Dream Chaser orbiting Earth at an altitude of 500 km with an inclination of 0 − 35◦ . This will be the first space mission dedicated to attaining the Sustainable Development Goals. In this investigation the South African space and aerospace industry is placed under the microscope for the purpose of studying the feasibility of landing the Dream Chaser Space Vehicle on South African soil. The research dictates possibly having to establish a dualuse airport/spaceport recognised by the South African Space Council under supportive legislation to support this mission. Elements addressed in this investigation range from physical facilities such as the airports, workshops and laboratories through Dream Chaser specific requirements and specifications, right down to space and civil aviation regulations. This dissertation will assess all available infrastructure and supporting entities that will facilitate the safe landing of the Dream Chaser space vehicle in South Africa. However site visits and interviews were not part of this investigation. This investigation prefaces the University of Cape Town's Space Lab plans to submit a landing proposal for a possible alternative landing site(s) for the Dream Chaser outside of the USA. This report is the first major step in researching and documenting the potential for landing the Dream Chaser or any reusable space vehicle in South Africa and will therefore make the case for South Africa as a suitable and attractive landing destination, not just for the Dream Chaser, but for accompanying scientists and researchers from all over the world involved in the mission.